A RETROSPECTIVE STUDY: ANALYSIS OF ADVERSE DRUG REACTION IN PEDIATRIC PATIENTS IN A TERTIARY CARE HOSPITAL - MATHUR, SUNIL KUMAR; JAIN, SAURABH KUMAR; MISHRA, AMUL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of this study was to analyze various parameters such as admission type, demographics, type of reaction, organ system classification, drugs involved, action is taken, reaction outcome, causality assessment, severity assessment, and the preventability of Adverse drug reactions (ADRs) in pediatric patients. Methods: This retrospective observational study was conducted during the period of September 2017 to June 2020 (34 months) at the ADR monitoring center, Department of Pharmacology, Jawaharlal Nehru Medical College, Ajmer, Rajasthan. All spontaneously reported ADRs were evaluated using various parameters such as type of reaction, causality assessment, preventability, and severity. Results: In the present study, 72 (7.27%) ADRs were reported in relation to 65 pediatric patients. In this study, more ADRs were reported in male (53.85%) as compared to female (46.15%) pediatric patients. The majority of ADRs were considered type B (63.89%), probable (87.5%), moderate (51.39%), and definitely preventable (88.89%) in nature. The majority of ADRs were reported due to antimicrobial classes of drugs, including anthelmintic drug (Albendazole), followed by glycopeptide antibiotic (Vancomycin) and third-generation cephalosporin antibiotics (Ceftriaxone, Cefotaxime, and Cefixime). The organ systems most commonly affected were skin and subcutaneous tissue disorders (47.22%), followed by general disorders and administration site conditions (20.83%) and gastrointestinal disorders (16.67%). Conclusion: The present study 30 different types of suspected ADRs that were reported with multiple frequencies, with included 34 different categories of drugs and combinations of drugs. The majority of patients recovered, with associated ADR, after necessary medical intervention and management. Our purpose is to minimize the incidence rate of ADRs in the pediatric population.